The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s00431-014-2423-2
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness is increased in asthmatic children

Abstract: Arterial stiffness is increased in children with mild-to-moderate asthma. The association between impaired lung function and increased arterial stiffness suggests that severity of disease translates into detrimental effects on the cardiovascular system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 24 publications
(28 reference statements)
0
18
1
Order By: Relevance
“…On the other hand, there is a scarcity of published data on the association between the childhood-onset asthma and atherosclerosis and only few studies evaluated elasticity in asthmatic children to date. Steinmann et al [16] showed an increased arterial stiffness in children with asthma using carotid-femoral pulse wave velocity measurements. Weiler et al [17] examined the arterial stiffness in peripheral large and small arteries and found no difference between the asthmatic adults and controls.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is a scarcity of published data on the association between the childhood-onset asthma and atherosclerosis and only few studies evaluated elasticity in asthmatic children to date. Steinmann et al [16] showed an increased arterial stiffness in children with asthma using carotid-femoral pulse wave velocity measurements. Weiler et al [17] examined the arterial stiffness in peripheral large and small arteries and found no difference between the asthmatic adults and controls.…”
Section: Discussionmentioning
confidence: 99%
“…[24] Meanwhile, an inverse correlation between FEV 1 and CFPWV in pediatric patients with mild-to-moderate asthma was demonstrated. [25] Patients with chronic obstructive pulmonary disease also have significantly higher CFPWV values. [24] Interestingly, decreased FEV 1 was shown to be significantly associated with enhanced arterial stiffness, as assessed by peripheral pulse pressure in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that a concurrent family history of hypertension and the frequency of attack of acute severe asthma did not seem to designate the status of blood pressure (21). Based on an earlier study, Steinmann et al found that arterial stiffness increased in children with mild and moderate asthma (22). Brachial-ankle pulse wave velocity tends to increase as the pathogenic condition aggravated in asthma (23).…”
Section: Discussionmentioning
confidence: 99%